Fallopian tube carcinoma mimicking inguinal hernia: A case report with imaging and histological insights - Anna Murata; Rika Yoshida; Shota Kato; Hideyuki Nagai; Minako Maruyama; Takeshi Yoshizako; Masako Ishikawa; Mamiko Nagase; Yasushi Kaji (Radiology Case Reports)
Fallopian tube carcinoma, presenting as an inguinal hernia, is a rare entity. We report the case of a woman in her 70s with a history of hysterectomy and right oophorectomy 29 years prior who presented with left cervical lymphadenopathy and elevated CA125 levels. Imaging revealed a tubular structure in the left pelvic region extending into the inguinal hernia sac. Contrast-enhanced computed tomography revealed a tubular structure with solid components in the left pelvic region that herniated through the left inguinal canal. Magnetic resonance imaging further characterized the solid component within the tubular structure and revealed features suggestive of malignancy. Fluorodeoxyglucose positron emission tomography/computed tomography revealed fluorodeoxyglucose uptake in the solid component and multiple enlarged lymph nodes, indicating lymph node metastasis. Subsequent laparoscopic resection confirmed high-grade serous carcinoma originating from the fallopian tube. Fallopian tube carcinoma typically presents nonspecific symptoms but elevated CA125 levels. Imaging often shows sausage-shaped masses. The mechanism in this case involved increased mobility of the left adnexa after hysterectomy and tumor infiltration near the inguinal canal. This case highlights the importance of considering fallopian tube carcinoma as a differential diagnosis when evaluating inguinal hernias, particularly in high-risk patients.